Ensuring human resource capacity to secure agricultural transformation - Beintema, Nienke M.; Elliott, Howard (International Food Policy Research Institute, 2016)
The preceding sections have assessed existing human resource capacity in SSA and key vulnerabilities needing urgent attention; the ability to build human resource capacity, however, depends on the longer-term financial and institutional capacities to do so, and on the supporting or limiting factors inherent in the policy environment. This section addresses the kinds of policy and institutional measures needed to support the development of human resource capacity in agricultural research across the region.